Rhetoric: Spoken discourse, A systematic appeal for reasoning "Pathos" - Adel Farid, Marwa M. (AUC Knowledge Fountain, 2015)
The tekhnē of spoken discourse is a critical tool for particular communications and is a substantial means to transform good knowledge . It is an objective tekhnē with an ergon, which is man-made. As such, it may be implemented for political, religious, social or educational purposes. Thus, understanding the implications of spoken discourse and establishing a shared understanding between the rhētōr and his listeners is not just an option in this context. On the contrary, both elements are the mind/soul/heart of the discourse. For what is the value of a discourse if its implications and representations are not well perceived by its listeners? Why do we care to convey knowledge of the good, if we cannot construct an intellectual connection between the listeners and us? I believe it would be impossible to attain any tangible outcomes from such an experience without initiating a discourse that contains these two elements. On the other hand, these two elements involve two concurrent prerequisites, which are: (1) the knowledge of the good, and (2) the good knowledge of the tekhnē. Consequently, converting the knowledge of the good using the good knowledge of the tekhnē are other central elements of the spoken discourse. Any rhētōr must exert all possible efforts to craft his argument using a reasonable form of rhetorical reasoning. Any proficient rhētōr can convey his particular knowledge to his listeners through this exclusive medium. His acquisition of the three skills , namely: (1) ēthos, (2) logos, and (3) pathos, are his means to reach the minds of his listeners in their various states. Furthermore, probability in rhetorical reasoning is not at all an enemy to strict logic. It also does not deconstruct universality. The natural capability of the human mind to use common opinions or common sense to perceive and infer the self-evident is not against logic, reason, knowledge and truth. Chaïm Perelman explains this further by affirming that: "It is the idea of self-evidence as characteristic of reason, which we must assail, if we are to make place for a theory of argumentation that will acknowledge the use of reason in directing our own actions and influencing those of others. Self-evidence is conceived both as a force to which every normal mind must yield and as a sign of the truth of that which imposes itself because it is self-evident. The self-evident would connect the psychological with the logical and allow passage back and forth between these two levels. All proof would be reduction to the self-evident and what is self-evident would have no need of proof" (The New Rhetoric: A Treatise of Argumentation 1969, 3-4). Correspondingly, intensifying the emotional states of the mind – pathos – using rhetorical spoken discourse has its power; and it is reasonable too. Our faculties of the mind are our means to rationally cognize the cultural environment we exist in – including the emotion states that we experience. Moreover, according to several recently developed theories of the faculties of the mind, there is an intelligible connection between the faculty of reason, the faculty of judgement and the faculty of emotions. The meaningful emotional behaviors and their potential institution of beliefs and actions are quite remarkable. The exemplary developments presented earlier in this research through a theological perspective , a rational perspective , and a social perspective assert and amplify the important role of pathos for exerting a potential change in the status-quo of the listeners by means of reason. Finally, it is apparent from the discussed reflections on the first and the second objectives of this thesis that a knowledgeable spoken discourse cannot afford to delete the emotional appeal – pathos – from its situational circumstances. Although reason and emotional appeal appear to be mutually exclusive, they support each other. The emotional appeal addresses the human mind in its particular states. In addition, the emotional appeal is one of the critical tools to potentially motivate both: change and action through any objective rhetorical spoken discourse.